Joseph Conrad and the reader questioning modern theories of narrative and readership - Acheraïou, Amar (Palgrave Macmillan, 2009)
"Joseph Conrad and the Reader is the first book fully devoted to Conrad's relation to the reader, visual theory and authorship. This challenging study proposes new approaches to modern literary criticism and deftly examines the limits of deconstructionist theories, introducing groundbreaking new theoretical concepts of reading and reception"--Provided by publisher.